MERANCANG PENDIRIAN BISNIS BARU DALAM RANGKA MENINGKATKAN PROFITABILITAS DAN KELAYAKAN KEUANGAN STUDI KASUS PADA BISNIS SALON KECANTIKAN “AMARANTH BEAUTY SALON” - Sally Nathania; Petrus Pius Salamin (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
This study aims to desingn a business plan for a new business as a guide for the business’ owner, in dayly operating, and in enhancing profiitability and financial feasibility of the business. The data used in this analysis is the projection data, either cost and price, for the next five (5) years. Method used in determining the market opportunity and sales is opinion methods and market survey. It is projected that sales(in unit) in the first year,2019, is 5.566, and it is estimated to increase to 9.735, in 2023, with an average growth of 15% per year. Profits obtained during 2019 amounted to Rp162.266.766,00, and it is projected to increase to Rp 695.009.186,00 in 2023. When viewed from its NPV, this business is feasible to run because the NPV is positive. Meanwhile, Payback period is only 3.67 months.